1983
DOI: 10.1159/000115542
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Whole Blood of Multiple Sclerosis

Abstract: Fe, Zn, and Cu were determined by atomic absorption spectrometry in samples of whole blood after weighing and wet ashing with HNO3. 35 healthy persons were compared with 119 multiple sclerosis (MS) patients and 13 patients with other diseases of the CNS. The values from normal persons are in full agreement with those cited in the literature, men showing a significantly higher level of Fe than women, whereas for Zn and Cu there is no significant sex difference. In comparison with the reference group the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Melø et al (2003) found an increase of Cu and a decrease of Mn levels in cerebrospinal fluid (CSF) in MS patients compared to controls, and no differences were found for Zn. Normal values for Fe, K, Na, Rb, Ca and Mg have been reported in blood or CSF (Palaviskas and Schulten 1984, Palm and Hallmans 1982, LeVine et al 1999, Rieder et al 1983, Exley et al 2006. Recently, Tamburo et al (2015) found a lower concentration of Al, rubidium and a higher concentration of uranium in scalp hair samples in MS patients compared to controls.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Melø et al (2003) found an increase of Cu and a decrease of Mn levels in cerebrospinal fluid (CSF) in MS patients compared to controls, and no differences were found for Zn. Normal values for Fe, K, Na, Rb, Ca and Mg have been reported in blood or CSF (Palaviskas and Schulten 1984, Palm and Hallmans 1982, LeVine et al 1999, Rieder et al 1983, Exley et al 2006. Recently, Tamburo et al (2015) found a lower concentration of Al, rubidium and a higher concentration of uranium in scalp hair samples in MS patients compared to controls.…”
Section: Discussionmentioning
confidence: 95%
“…To the best of our knowledge, this is the first study comparing the 24 trace elements in the plasma of MS patients and compared with healthy volunteers. A limited number of studies have been published on the possible role of trace elements in MS (Melo et al 2003, Mauch et al 1995, Valberg et al 1989, Dore-Duffy et al 1983, Palavinskas and Schulten 1984, Palm and Hallmans 1982, LeVine et al 1999, Rieder et al 1983, Exley et al 2006, Forte et al 2005b and the results are inconsistent. Discrepancies among studies investigating the metals and trace elements in patients with MS may be attributable to small sample sizes that resulted in insufficient statistical power to detect some relationships in the individual studies.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have been published on the possible role of trace elements in MS [20,[27][28][29][30][31][32][33][34][35]. Melø et al [20] found increased Cu levels and decreased Mn in CSF in MS patients compared to controls, and no differences were found for Zn.…”
Section: Discussionmentioning
confidence: 99%
“…Melø et al [20] found increased Cu levels and decreased Mn in CSF in MS patients compared to controls, and no differences were found for Zn. Normal values for Fe, K, Na, Rb, Ca and Mg have been reported in blood or CSF [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that the concentrations of copper in serum (27) and whole blood (30) are normal in MS patients.…”
Section: B Coppermentioning
confidence: 99%